We need to appreciate common synanthropic plants before they become rare: Case study in Latgale (Latvia) - Prūse, Baiba; Kalle, Raivo; Buffa, Gabriella; Simanova, Andra; Mežaka, Ieva; Sõukand, Renata (Ethnobiology and Conservation, 2020)
Local ecological knowledge holds great potential in contributing to sustainable resource management and conservation activities. For this reason, the authors choose to analyse an ethnobotanical dataset from the Baltic Sea region by exploring the relationship between plants and humans on the basis of three main categories: habitat characteristics, distribution in the wild and plant sensitivity to human impact beyond physical distance. The study provides empirical evidence of widespread usage of so-called common species which are widely distributed in the territory and benefit from human activity. When considering the data via the intensity of use, based on detailed use-reports (DUR), the main category is shown to be apophytes (1001 DUR), followed by anthropophytes (426), hemeradiophores (255) and hemerophobes (54). The authors highlight the co-dependency of plants and humans in the medicinal and wild food domains and stress the need for integrated management strategies where local community knowledge plays a part. Keywords: Common Species; Conservation; Ethnobotany; Synanthropic Plants.